2021
DOI: 10.1111/jfbc.14010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights on chemopreventive and anticancer potential of carvacrol: Implications from solid carcinomas

Abstract: Globally, cancer is one of the deadliest diseases, estimated to cause 9.9 million deaths in 2020. Conventional cancer treatments commonly involve mono‐chemotherapy or a combination of radiotherapy and mono‐chemotherapy. However, the negative side effects of these approaches have been extensively reported and have prompted the search for new therapeutic drugs. Over the past few years, numerous dietary agents, medicinal plants, and their phytochemicals gained considerable therapeutic importance because of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 96 publications
1
14
0
Order By: Relevance
“…Plant species of the Lamiaceae family are rich in phenolic compounds and are mainly used as dried products for culinary purposes and herbal medicine [ 55 ]. Carvacrol, as a major component of these plants, has gained great scientific interest [ 15 ]. However, the application of carvacrol may be limited due to its volatile nature, low water solubility, and poor bioavailability due to its excretion after 24 h in urine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant species of the Lamiaceae family are rich in phenolic compounds and are mainly used as dried products for culinary purposes and herbal medicine [ 55 ]. Carvacrol, as a major component of these plants, has gained great scientific interest [ 15 ]. However, the application of carvacrol may be limited due to its volatile nature, low water solubility, and poor bioavailability due to its excretion after 24 h in urine.…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted in rats, the effect of Thymus vulgaris on antioxidant enzyme activity in various organs was investigated and it was found that T. vulgaris consumed as a dietary component reduced the age-related decline in superoxide dismutase enzymes in the liver and heart of aged rats [ 13 ]. One active substance representing a significant part of the essential oils of Lamiaceae plants is the monoterpenoid phenol carvacrol (5-isoropyl-2-methylphenol) [ 14 , 15 ]. Previously, it has been reported that carvacrol metabolizes fast due to its ring hydroxylation chemical structure, and is excreted after 24 h in the urine of rats [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemotherapeutic antitumor drugs used traditionally for the treatment of cancer patients showed high cytotoxicity to the tumor as well as normal tissues [ 55 , 58 ]. Therefore, searches for new therapeutic options, including medicinal plants and their phytochemicals, has been promoted due to their lower risk of side effects compared to standard chemotherapeutic drugs [ 59 ]. Numerous studies have demonstrated the beneficial effects of different medicinal plant extracts and their ability to exert damaging effects on cancer cells through various molecular mechanisms, including intrinsic or extrinsic caspase-dependent apoptosis, autophagy, and necroptosis [ 60 , 61 , 62 ].…”
Section: Biological Activity Of Thymementioning
confidence: 99%
“…Carvacrol and thymol exerted anticancer effects in various types of cell lines mimicking human cancers and they demonstrated their potential as chemopreventive or anticancer agents in different types of cancers [ 55 , 65 , 66 ]. Their major mechanisms of anticancer actions include induction of apoptosis, inhibition of cell growth (antiproliferative effect), augmentation of ROS generation, depolarization of mitochondrial membrane, activation of Bax proapoptotic mitochondrial proteins, inhibition of angiogenesis, interaction with caspase or poly-ADP ribose polymerase, and diminution of tumorigenesis by modulating the activity of carcinogen metabolizing enzymes [ 59 , 65 , 67 ].…”
Section: Biological Activity Of Thymementioning
confidence: 99%